An In-depth Review of Cutaneous Necrotizing Venulitis: Clinical and Pathological Perspective - Hazlianda, Cut Putri; Putri Harahap, Rima Rahmi (SCRIPTA SCORE Scientific Medical Journal, 2025)
Background: Cutaneous Necrotizing Venulitis (CNV) is a complex multisystem disorder primarily affecting small skin vessels, particularly postcapillary venules. Objective: This article aims to discuss about cutaneous necrotizing venulitis (CNV). Methods: This article was written by reviewing book and articles related with cutaneous necrotizing venulitis (CNV) which are obtained from several search engines such as Pubmed, Science Direct, and Google Scholar. Discussion: CNV usually manifests as palpable purpura on the skin and may also involve multiple organ systems, including the kidneys, gastrointestinal tract, pericardium, and nervous system. The etiology of CNV remains incompletely understood but is often associated with infections, drug reactions, systemic inflammatory diseases, and malignancies. Clinical manifestation of CNV is mainly palpable purpura, which is red purpura that does not disappear when the skin is pressed. Other lesions such as erythematous macules, papulonodular lesions, urticaria, angioedema, pustules, hemorrhagic vesicles and bullae, necrosis, ulcers, subcutaneous edema and livedo reticularis can also be found in CNV cases. Conclusion: Cutaneous Necrotizing Venulitis (CNV) is a complex disease primarily affecting the skin and mucous membranes. Diagnosis of CNV involves clinical evaluation and histopathological examination. Treatment strategies of CNV aim to address underlying triggers, manage systemic involvement, and suppress inflammatory responses using topical and systemic therapies such as corticosteroids, NSAIDs, and immunosuppressive agents. Treatment strategies of CNV aim to address underlying triggers, manage systemic involvement, and suppress inflammatory responses using topical and systemic therapies such as corticosteroids, NSAIDs, and immunosuppressive agents and CNV often exhibits a favorable prognosis with appropriate management.   Latar Belakang: Cutaneous necrotizing venulitis (CNV) adalah gangguan multisistem yang kompleks, terutama menyerang pembuluh darah kecil di kulit, khususnya venul postkapiler. Tujuan: Artikel ini bertujuan untuk memberikan analisis mendalam mengenai patogenesis, manifestasi klinis, diagnosis, dan strategi pengobatan CNV. Metode: Artikel ini didasarkan pada tinjauan literatur dari berbagai sumber ilmiah yang relevan, termasuk jurnal dan buku yang diakses melalui PubMed, ScienceDirect, dan Google Scholar. Pembahasan: CNV biasanya bermanifestasi sebagai purpura teraba pada kulit dan dapat melibatkan berbagai sistem organ, termasuk ginjal, saluran gastrointestinal, perikardium, dan sistem saraf. Etiologi CNV masih belum sepenuhnya dipahami, tetapi sering dikaitkan dengan infeksi, reaksi obat, penyakit inflamasi sistemik, dan keganasan. Manifestasi klinis utama CNV adalah purpura teraba, yaitu purpura berwarna merah yang tidak menghilang saat kulit ditekan. Lesi lain yang dapat ditemukan pada kasus CNV meliputi makula eritematosa, lesi papulonodular, urtikaria, angioedema, pustula, vesikel dan bula hemoragik, nekrosis, ulkus, edema subkutan, serta livedo reticularis. Kesimpulan: Cutaneous necrotizing venulitis (CNV) adalah penyakit kompleks yang terutama mempengaruhi kulit dan selaput lendir. Diagnosis CNV melibatkan evaluasi klinis dan pemeriksaan histopatologi. Strategi pengobatan CNV bertujuan untuk mengatasi pemicu yang mendasari, mengelola keterlibatan sistemik, serta menekan respons inflamasi menggunakan terapi topikal dan sistemik, seperti kortikosteroid, NSAID, dan agen imunosupresif. CNV umumnya memiliki prognosis yang baik dengan penanganan yang tepat.  Keywords: angiitis nekrotikans, vaskulitis, venulitis, venulitis nekrotikans kutan